Performance of halophytes in soil desalinization and its influencing factors: a meta-analysis - Wang, Shiqi; Liu, Jinbiao; Wang, Yanyan; Liu, Yalan; Tian, Changyan (Frontiers in Environmental Science, 2023)
Soil salinization threatening natural and agricultural production challenges global food security.Halophytes are of great interest in soil desalinization in recent years; yet, there is a lack of a comprehensive quantitative overview of biotic and abiotic factors for halophytes' desalinization performance across global scales. Here, a meta-analysis was conducted using 400 observations from 53 peer-reviewed studies to assess desalinization by halophytes in relation to 27 variables. Results showed that soil salinity was significantly decreased in halophytes field on average by 37.7% compared to control on a global scale (p < 0.05). Desalinization performance was better in cold and hot regions than in temperate regions, in dry regions than in wet regions, in alkaline saline soils than in neutral saline soils, and in conditions with low sand content than high sand content. Under aboveground harvest treatment, desalinization increased with the years of cultivation, while no trends were detected under no harvest treatment, indicating the importance of aboveground accumulation. Desalinization was not related to soil CaCO3 content but was accompanied by soil structure improvement, nutrition enrichment, and microbe propagation, implying other root-microbe-soil interactions rather than CaCO 3 dissolution play important roles. Shoot biomass could be used as an indicator of the desalinization performance, and the performance would not be decreased due to the high uptake selectivity for K + over Na + . Notably, desalinization was similar in the pot experiments and field experiments, but pot experiments would magnify the contribution of aboveground salt accumulation to desalinization. Our findings can help to expand the applicability and efficiency of halophytes for sustainable agricultural development in saline soils.